2023
DOI: 10.3390/foods12081725
|View full text |Cite
|
Sign up to set email alerts
|

Storability and Linear Regression Models of Pericarp Browning and Decay in Fifty Litchi (Litchi chinensis Sonn.) Cultivars at Room Temperature Storage

Abstract: The primary cause for the limited shelf life of litchi fruit is rapid pericarp browning and decay. This study aims to evaluate the storability of 50 litchi varieties and establish a linear regression model for pericarp browning and decay based on 11 postharvest physical and chemical indices after 9 days of storage at room temperature. The results indicated that the average value of the browning index and decay rate significantly increased to 3.29% and 63.84% of 50 litchi varieties at day 9, respectively. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…MLR can not only be used to establish the relationship between spectral VIs and the crop characteristics studied but also to select the most informative variables to estimate crop characteristics [26]. Previously published studies have reported that MLR is a widely used method to rapidly estimate leaf crop nitrogen concentrations [27,28] and grain yields [29,30], whereas PCA, HCA and MLR are also used as important indicators to evaluate lychee browning and rot [31].…”
Section: Introductionmentioning
confidence: 99%
“…MLR can not only be used to establish the relationship between spectral VIs and the crop characteristics studied but also to select the most informative variables to estimate crop characteristics [26]. Previously published studies have reported that MLR is a widely used method to rapidly estimate leaf crop nitrogen concentrations [27,28] and grain yields [29,30], whereas PCA, HCA and MLR are also used as important indicators to evaluate lychee browning and rot [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, most cultivars ripen between mid-June and mid-July, leading to a centralized fruit maturation period [6,7]. Furthermore, pericarp browning and aril decay develop rapidly once the litchi fruit has been detached from the tree [8][9][10], resulting in an extremely short shelf life. Therefore, the breeding of novel litchi cultivars with more diverse fruit maturation periods (like extremely early or extremely late) and better storability after harvest, as well as improvement of other traits like fruit quality, disease resistance, adaptations to climate changes and etc., has become increasingly important for the sustainable development of the litchi industry in China [11].…”
Section: Introductionmentioning
confidence: 99%